2011
DOI: 10.1109/tbme.2010.2096507
|View full text |Cite
|
Sign up to set email alerts
|

Design and Test of a Novel Closed-Loop System That Exploits the Nociceptive Withdrawal Reflex for Swing-Phase Support of the Hemiparetic Gait

Abstract: A novel closed-loop system for improving gait in hemiparetic patients by supporting the production of the swing phase using electrical stimulations evoking the nociceptive withdrawal reflex was designed. The system exploits the modular organization of the nociceptive withdrawal reflex and its stimulation site- and gait-phase modulation in order to evoke movements of the hip, knee, and ankle joints during the swing phase. A modified model-reference adaptive controller (MRAC) was designed to select the best stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In a study involving a single training session, it was shown that a more functional hemiparetic gait could be obtained by eliciting the lower limb NWR by electrical stimulation of the sole of the foot in order to obtain preset kinematic goals [28]. In the present study, the therapeutic effect of a NWR-FET system was studied and it was shown that although the system was very simple, consisting of an open-loop one channel stimulator, it succeeded to produce an effect that outlasted the training period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study involving a single training session, it was shown that a more functional hemiparetic gait could be obtained by eliciting the lower limb NWR by electrical stimulation of the sole of the foot in order to obtain preset kinematic goals [28]. In the present study, the therapeutic effect of a NWR-FET system was studied and it was shown that although the system was very simple, consisting of an open-loop one channel stimulator, it succeeded to produce an effect that outlasted the training period.…”
Section: Discussionmentioning
confidence: 99%
“…It has therefore been suggested that electric stimulation of the sole of the foot could be used to initiate and facilitate the swing phase of the hemiparetic gait [27]. The use of both an open-loop, single channel stimulator and a closed-loop system that selects the optimal stimulation parameters resulted in a more functional gait of hemiparetic individuals during a single training session [28], indicating that this modality of stimulation might benefit gait training.…”
Section: Introductionmentioning
confidence: 99%
“…Predefined, or open‐loop, stimulation patterns are therefore limited in their ability to produce desired movement patterns and the limitations are magnified by the high rate of fatigue of electrically stimulated muscle . Adaptive control strategies have been developed to help account for the variability observed across individuals and for muscle fatigue . If successful, this type of control accurately produces the desired motion in a highly repeatable manner and may therefore maximize the therapeutic benefits of electrical stimulation.…”
Section: Physiological Response To Spinal Cord Injurymentioning
confidence: 99%
“…[64][65][66] Adaptive control strategies have been developed to help account for the variability observed across individuals and for muscle fatigue. 65,[67][68][69][70] If successful, this type of control accurately produces the desired motion in a highly repeatable manner 66 and may therefore maximize the therapeutic benefits of electrical stimulation.…”
Section: Electrical Stimulationmentioning
confidence: 99%
“…A more functional gait has been obtained during a single training session when using both, an open-loop, single channel stimulator and a closed-loop system that selects the stimulation site and timing [14], suggesting that this modality of stimulation might benefit gait training.…”
Section: Introductionmentioning
confidence: 99%